L'« affaire des omelettes » et ses conséquences sur le partage des compétences législatives en matière de taxation et de commerce - Bourque, Denis (Les Cahiers de droit, 1978)
The Supreme Court of Canada has recently rendered judgment in what has come to be known as the Omelet Case. The Court was called upon to rule on the constitutionality of several provisions in federal and Ontario law, the purpose of which was to set up a plan for the marketing of eggs in Canada. The plan provided for a levy on producers and had as its objectives the attribution to each province of a share of the national market for eggs, and the setting of production quotas within each province as regards its part of the market. Such quotas were to be set in an identical manner for all producers, whether they be engaged in intraprovincial, inter provincial, or export trade. The province of Ontario also provided for the imposition of quotas as to the means of production, particularly as to the number of domestic hens a producer could possess. This paper shows how the distribution of legislative powers in respect of taxation and commerce is affected by the Supreme Court's decision. It is suggested that the Court has completely abandoned the doctrine of the Crystal Dairy case, in which the Privy Council had ruled that the levying of fees on producers was a matter of taxation. The paper also outlines the consequences of certain remarks by Chief Justice Laskin on the spending power of Parliament. The paper then discusses the reticence of certain members of the Court to approve the measures adopted by Ontario concerning the control of means of production. Such reticence illustrates the difficulties faced by the Court when trying to define or identify which measures can be adopted by the provinces, within the framework of agricultural marketing plans, without encroaching upon federal jurisdiction over interprovincial trade under subs. 91(2) of the BNA Act. Finally, the paper attempts to show how the scope of s. 121 of the BNA Act is limited by the ruling that it cannot hamper federal regulation of interprovincial trade under subs. 91(2). This latest decision confirms the broadening of the scope of subs. 91(2), already apparent in the Caloil case and the Manitoba Egg reference. The strenghtening of subs. 91(2) may imply that s. 121 will be applied differently, according to whether federal or provincial legislation is involved.